Sibbar (Situs Belajar Bahasa Arab) : Pengembangan Media Pembelajaran Keterampilan Membaca Berbasis Linktree Untuk Siswa Kelas IV MI di Kota Semarang - Hilmi Ana Utami; Akbar Syamsul Arifin; Zaim Elmubarok; Ahmad Hasyim, Mohamad Yusuf (Universitas Negeri Semarang, 2024)
Education always adapts to technological advances, especially in learning Arabic reading skills. For this reason, teachers must innovate and be creative in designing learning media for Arabic reading skills, one of which is the development of linktree-based Sibbar (Arabic Language Learning Site). The problems studied in this study are:(1) how to analyze the needs of teachers and students for linktree-based Sibbar (Arabic Language Learning Site), (2) how to prototype linktree-based Sibbar (Arabica Language Learning Site), (3) how to validate experts and teachers against linktree-based Sibbar (Arabic Language Learning Site). This research uses mixed method research and uses research and development (R&D) research design with the ADDIE model without the implementation stage, so this research only uses four stages (Analysis, Design, Development, and Evaluation). Data collection techniques in thist study were questionnaires, interviews, and documentation. The data validity test uses triangulation of techniques and sources. The results of this study are: First, teachers and students approved the development of linktree-based Sibbar (Arabic Language Learning Site) media. Second, this media prototype contains an initial display in the form of a menu page that contains several links on one landing page. Consists of (1) linktree account name (2) student attendance connected directly to google form, (3) Learning Outcomes, Learning Objectives, Learning Objectives Flow and indicators and indicators (4) Arabic learninga materials, containing mufrodat (vocabulary) materials and reading texts in the form of learning videos connected directly to google drive, (5) rules in the form of learning videos connected directly to google drive, (6) online game quizzes connected directly to the educandy website, (7) exercises. Third, the assessment on the media aspect obtained a total average score of 3.90 and the material aspect obtained a total average score of 3.89. The recapitulation of Sibbar (Arabic Language Learning Site) media value based on linktree is 3.89 with the category very feasible / very suitable, so it can be used for learning Arabic reading skills of grade 4th elementary school.